THE SCOPE OF THE SUBJECT IN JADID POETRY - Bekmurodova Rukhshona Eldar kizi (Bright Mind Publishing, 2025)
This article analyzes the form and subject matter of poetic works created during the Jadid period. The ideas of enlightenment in them and the main ideas put forward are taken into account.
Keywords: Jadidism, poetry, verse, enlightenment, knowledge, ignorance, Abdulla Qodiriy, Cholpon, Is'hoqkhon Tora Ibrat, Avloniy, spirituality, perfection.